2020
DOI: 10.37624/ijert/13.3.2020.444-453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Percentage Weight and Particle Size of SiCp Reinforcement on the Mechanical Behaviour of Functionally Graded Aluminum Metal Matrix Composite

Abstract: The fabrication of functionally graded aluminum metal matrix composite with varying properties using a centrifugal casting technique was carried out using silicon carbide particles (SiCp) of an average particle size of 15 µm as reinforcement. The effect of the SiCp reinforcements at different weight-percent on the hardness and tensile properties of A356 aluminum alloy was studied. The effect of particle size of the SiC reinforcement on the properties of the aluminum alloy was also investigated. It was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This result is in agreement with previous studies reported for FGMs processed by centrifugal casting. 911,2123 The image analysis results depicted in Figures 5 and 6 show that with increasing rotational speed, the concentration of the SiC particles in the outer layers increased, and the volume fraction of SiC in the inner layers at high rotation speeds decreased to zero.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This result is in agreement with previous studies reported for FGMs processed by centrifugal casting. 911,2123 The image analysis results depicted in Figures 5 and 6 show that with increasing rotational speed, the concentration of the SiC particles in the outer layers increased, and the volume fraction of SiC in the inner layers at high rotation speeds decreased to zero.…”
Section: Resultsmentioning
confidence: 98%
“…In the case of other mechanical and thermal properties, little experimental work has been done. The effect of SiC particle reinforcement on the strengthening of A359 Al alloys was studied experimentally by tensile testing specimens with different SiC contents by Rodrıa¨guez-Castro et al 21 and Owoputi et al 23 In another work by Aydın et al, 4 the Young's modulus (E) and YS for Al/ SiC FGMs has been investigated. The use of a vibration during the production of FGMs has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally Graded Materials are composites with a heterogeneous microstructure with mechanical properties changing smoothly and continuously from one side to other side. In other words, mechanical properties also change continuously through thickness according to the type of composition [2,3]. Ceramic/metal composites have found the widest application among FGMs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this smooth gradient of the change of the composition of the FGMs ingredients, they exhibit higher mechanical properties compared to the laminated composite materials. On the other hand, functionally graded materials exhibit different properties in different regions due to the gradual change of their composition, distribution, orientation, or size of the reinforcing phase in one or more directions, leading to continuous stress gradients and improved strength [3].…”
Section: Introductionmentioning
confidence: 99%
“…gradient functional thin films, are used in many fields. [16][17][18][19][20][21][22] For example, it is difficult and expensive to machine effective cutting tools from a single hard material, such as diamond. The use of gradient functional thin films lowers the costs of such cutting tools by applying high-hardness thin films to the surface of an easily machinable material.…”
Section: Introductionmentioning
confidence: 99%